Inter-disks inversion surfaces - D. Pugliese; Z. Stuchlík (European Physical Journal C: Particles and Fields)
Abstract We consider a counter-rotating torus orbiting a central Kerr black hole (BH) with dimensionless spin a, and its accretion flow into the BH, in an agglomerate of an outer counter-rotating torus and an inner co-rotating torus. This work focus is the analysis of the inter-disks inversion surfaces. Inversion surfaces are spacetime surfaces, defined by the condition $$u^{φ }=0$$ u ϕ = 0 on the flow torodial velocity, located out of the BH ergoregion, and totally embedding the BH. They emerge as a necessary condition, related to the spacetime frame-dragging, for the counter-rotating flows into the central Kerr BH. In our analysis we study the inversion surfaces of the Kerr spacetimes for the counter-rotating flow from the outer torus, impacting on the inner co-rotating disk. Being totally or partially embedded in (internal to) the inversion surfaces, the inner co-rotating torus (or jet) could be totally or in part “shielded”, respectively, from the impact with flow with $$a u^{φ }<0$$ a u ϕ < 0 . We prove that, in general, in the spacetimes with $$a<0.551$$ a < 0.551 the co-rotating toroids are always external to the accretion flows inversion surfaces. For $$0.551<a<0.886$$ 0.551 < a < 0.886 , co-rotating toroids could be partially internal (with the disk inner region, including the inner edge) in the flow inversion surface. For BHs with $$a>0.886$$ a > 0.886 , a co-rotating torus could be entirely embedded in the inversion surface and, for larger spins, it is internal to the inversion surfaces. Tori orbiting in the BH outer ergoregion are a particular case. Further constraints on the BHs spins are discussed in the article.